Root triterpenoid metabolites drive the assembly and feedback regulation of the rhizosphere microbiome during flowering to senescence in Rhododendron hybridum ‘Yangmeihong’ - Shan, Fei; Leng, Chenxi; Xiao, Yufeng; Zhang, Ximin; Tang, Ming; Yi, Yin; Tang, Jing (Frontiers in Microbiology, 2026)
The flowering-to-senescence transition is a critical developmental period in ornamental plants, yet the interplay between root metabolites and the rhizosphere microbiome during this process remains poorly characterized. Integrating metabolomic and microbiomic analyses of Rhododendron hybridum, we investigated their dynamic interactions. Our analyses revealed both the root metabolome and rhizosphere microbiome exhibited significant temporal dynamics. Differential metabolites significantly enriched in sesquiterpenoid and triterpenoid biosynthesis, while microbial α-diversity peaked at full bloom before declining. The rhizosphere microbial network complexity decreased from flowering to senescence, accompanied by a shift in community assembly from stochastic to more deterministic processes. Furthermore, root metabolites mediated stage-specific assembly of the rhizosphere microbiome. Specifically, seven volatile terpenoids, upregulated during senescence, were significantly correlated with 77 microbial taxa, including putative plant growth-promoting bacteria. Functional prediction suggested that these interacting microbial taxa are potentially involved in sulfur cycling, methionine biosynthesis, and nucleic acid metabolism, indicating a potential role in feedback regulation during senescence. Our findings demonstrate that root triterpenoid metabolites are pivotal in driving rhizosphere microbiome assembly and may receive functional feedback, providing novel insights into microbiome-mediated regulation of floral development and senescence.